The Impact of Human Capital on Assets Profitability: Evidence from Enterprises in Kosovo - Goga, Arta Jashari; Mehmeti, Ismail; Krasniqi, Sokol (Journal of Cultural Analysis and Social Change, 2025)
This study explores how small and medium-sized enterprises (SMEs) in Kosovo can enhance their asset profitability by strategically managing human capital through key human resource management (HRM) practices, including flexible rewards, job stability, equality, and employee involvement. Data were collected from Kosovo SMEs using a structured survey and analyzed through advanced statistical techniques to examine the relationships between HRM practices and assets profitability. Using assets profitability as an objective indicator of organizational performance provides a clear link between human capital management and financial outcomes. Our findings reveal that HRM initiatives significantly enhance employee performance, which in turn positively influences assets profitability. Employee involvement, emerged as the most influential practice in driving both employee and financial success. The results highlight the critical importance for SME managers to strategically invest in HRM approaches to maximize employee potential and strengthen asset-based financial performance. Also, can foster long-term growth, competitiveness, and organizational resilience. This study reflects the state of enterprises in a developing economy such as Kosovo, which faces numerous challenges in the effective management of its most valuable resource. In this context, we analyzed the approaches these enterprises apply and the benefits they gain from them. Additionally, the study contributes to the literature by integrating a financial performance indicator into HRM strategy.